PROFIL TEKNOLOGI BUDIDAYA BANDENG (Chanos chanos) DI PUJUT KABUPATEN LOMBOK TENGAH: The Profile Of Milkfish Cultivation Technology (Chanos Chanos) In Pujut Central Lombok Tengah District - Tohirman, Tohirman; Hamid, Hamid; Asrial, Evron; Tarmizi, Azhari (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2024)
Milkfish cultivation with traditional technology in Mertak Village only lasts one cycle per year. The limited cycle of milkfish cultivation causes it to be less desirable, even though the profit level is quite high. For this reason, this study aims to study the key variables of cultivation and estimate the feasibility of the milkfish cultivation business. This research was conducted in Mertak Village, Central Lombok. used in this research is descriptive survey, and data collection using census method. Data analysis uses Regression-Correlation which aims to predict the determination / influence of the independent variable (X) on the dependent variable (Y). The results of the technical evaluation of milkfish cultivation in the village of Mertak amounted to 563 kg/ha/cycle with the size of the milkfish harvesting 8 individuals/kg. In addition, averange body weight (ABW) of 125 grams/individual was obtained, survival rate (SR) reached 53.68%, and FCR 0.23. The results of the business feasibility analysis show the value of the Benefit-Cost Ratio (B/C Ratio) = 2.218, which means that the milkfish cultivation business is feasible to continue because the B/C ratio is >1.0. The milkfish cultivation activities in Mertak Village, Pujut Subdistrict, Central Lombok Regency have followed the rules of good aquaculture practice (GAP). The milkfish farmers consistently run their business to increase pond productivity.